Lightweight Zero Knowledge Authentication for Internt of Things - Beydemir, Alican; Soğukpınar, İbrahim (IEEE, 2017)
Importance of Internet of Things technologies increased in recent years. However, these technologies carry some security vulnerabilities because of their network communication layer. The root cause of these vulnerabilities is usually the Authentication problem. Zero knowledge proof method is a strong cryptographic solution for Authentication problem that is proving of having a knowledge to another party without revealing anything other than the veracity of the statement. Zero knowledge proof method is consist of two-way complex mathematical algorithms for both parties. In this work, a new method that uses zero knowledge proofs has been proposed to provide efficient solution for Internet of Things technologies. New method was implemented and tested, then compared with existing proposed zero knowledge proof based authentication methods.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: Cryptology; Authentication; Zero Knowledge Proof; Internet of Things